Pembangunan mampan pelancongan maritim di pantai timur semenanjung Malaysia - Hanizah Idris; Hanizah Hj. Idris; Norhaslina Hassan; Safiah @ Yusmah Muhammad Yusoff; Asra Zaliza Asbollah; Muhammad Faiz Ramli (Penerbit Universiti Malaya, 2017)
On development of marine ecotourism in the eastern part of Malaysia and its impact on the environment and communities